CFD performance analysis for Darrieus Hydrokinetic Turbine (2019)
This work proposes the analysis of the behavior of a Darrieus type hydrokinetic turbine, starting from the mathematical model that allows to delimit the operation system, linking all the variables present in the phenomenon, specifically the fluid properties such as density, velocity, viscosity and Reynolds number. Also considered are the geometric data of the profiles, the rope length, cross-sectional area, angle of attack of the impeller, type of profile used and speed of rotation. The initial domain data, the flow area and the boundary conditions are selected to solve the model and thus obtain the data of the individual behavior of the selected profiles. For this, the lift and drag curves are obtained over a wide range of angles of attack. After characterizing the profile, the behavior of the impeller is simulated, calculating its power coefficient and consequently its performance.